Commissioning of new FHCal at BM@N experiment. Issue 1 (1st November 2022) - Izvestnyy, A; Golubeva, M; Guber, F; Ivashkin, A; Karpushkin, N; Morozov, S; Petukhov, O
Abstract : The BM@N (Baryonic Matter at Nuclotron) is the fixed target experiment at NICA-Nuclotron (JINR, Dubna, Russia) accelerator complex. The main goal of the experiment is studying the properties of dense nuclear matter produced in ion-ion collisions at the energies of up to 4 AGeV. New Forward Hadron Calorimeter (FHCal) with modular structure and a beam hole in the center has been developed and constructed to measure the collision centrality after the BM@N upgrade. The transverse and longitudinal segmentation of the FHCal allows to perform calibration of the calorimeter with cosmic muons. FHCal modules have lead/scintillator sampling structure with longitudinal segmentation. Light signals from the sections are collected with MPPCs, amplified and read-out by ADC boards. Fast analog signals are collected for trigger system. The status of development and construction of the new FHCal calorimeter for the BM@N experiment is presented. Performance of FHCal front-end and readout systems is discussed.